On the taxonomic status of the genus Horvathinia Montandon (Hemiptera: Belostomatidae) - Schnack, Juan A.; Estévez, Ana L. (Zootaxa, 2005)
Nine species of Horvathinia have been described since Montandon (1911) described H. pelocoroides, a description based upon two specimens. Subsequent descriptions, of H. argemii Schnack, H. bollei De Carlo, H. castilloi De Carlo, H. doellojuradoi De Carlo, H. forsteri Lauck, H. lenti De Carlo, H. meyeri De Carlo, H. pelleranoi De Carlo, and H. schubarti De Carlo, were based on only one specimen, each all captured while flying at lights. In February 1981, 55 specimens of Horvathinia were collected flying at light in Torres, Rio Grande do Sul, Brazil. The morphological variation of these specimens is similar to that diagnostic species-level characters in describing Horvathinia species. Therefore, we consider that the southern South American genus Horvathinia is monotypic. However, as far as the type of H.lenti could not be examined, we therefore synonymize all species described after 1911 with H. pelocoroides, except for H. lenti. We also redescribe H. pelocoroides Montandon.